Baby mammoth mummy : frozen in time! : a prehistoric animal's journey into the 21st century - Sloan, Christopher (National geographic kids, 2011)
Tells the story of the discovery of Lyuba, a perfectly preserved baby mammoth discovered along a river in Siberia 31,000 years after her birth, and offers a glimpse into her prehistoric world.